2008
DOI: 10.1186/1477-7819-6-58
|View full text |Cite
|
Sign up to set email alerts
|

Male breast cancer: is the scenario changing

Abstract: There is a scenario of rising incidence, particularly in urban US, Canada and UK. Even though more data on risk factors is emerging about this disease, more multi-institutional efforts to pool data with large randomized trials to show treatment and survival benefits are needed to support the existing vast emerging knowledge about the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
108
3
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(122 citation statements)
references
References 129 publications
(121 reference statements)
5
108
3
6
Order By: Relevance
“…In our study five year survival of men with breast cancer in relation to stage of the disease is much lower and amounts to 100% for T1 stage of the disease, T2 stage 87%, T3 stage 38%, while for T4 stage 0%. In numerous studies the clinical stage of disease is identified as a significant independent prognostic factor for survival of men with breast cancer (Vaizey et al, 1999), and even as a separate risk factor independent from tumor size or lymph node metastasis (Contractor et al, 2008;Schaub et al, 2008;Gomes-Raposo et al, 2010). In our study, a lower initial disease stage, a lower tumor grade, application of adjuvant hormone therapy and no relaps occurrence were independent predictors of a favorable outcome of breast cancer in males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study five year survival of men with breast cancer in relation to stage of the disease is much lower and amounts to 100% for T1 stage of the disease, T2 stage 87%, T3 stage 38%, while for T4 stage 0%. In numerous studies the clinical stage of disease is identified as a significant independent prognostic factor for survival of men with breast cancer (Vaizey et al, 1999), and even as a separate risk factor independent from tumor size or lymph node metastasis (Contractor et al, 2008;Schaub et al, 2008;Gomes-Raposo et al, 2010). In our study, a lower initial disease stage, a lower tumor grade, application of adjuvant hormone therapy and no relaps occurrence were independent predictors of a favorable outcome of breast cancer in males.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of breast cancer in male has been hardly studied, because the disease is very rare (Weiss et al, 2005;Contractor et al, 2008;Schaub et al, 2008). However the incidence of breast cancer in male's population is on the constant increase (Weiss et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As summarized in [1], a higher positivity rate of estrogen and progesterone receptors (ER and PgR) in MBC respect to FBC is well established. However, Munoz de Toro et al [5] remarkably found that in MBC proliferation rate was higher in ER+/PgR+ compared to ER-/PgR-tumors, an opposite finding respect to FBC which strongly support the hypothesis that these receptors may play a different role in males compared to women.…”
Section: Introductionmentioning
confidence: 99%
“…However, Munoz de Toro et al [5] remarkably found that in MBC proliferation rate was higher in ER+/PgR+ compared to ER-/PgR-tumors, an opposite finding respect to FBC which strongly support the hypothesis that these receptors may play a different role in males compared to women. Controversial data were reported for AR positivity as well as for ERBB2 amplification rate, with positivity rates ranging from 0 to 95% among different studies [1][2][6][7]. Furthermore, an immunohistochemical analysis of ER, AR and functionally related proteins indicates a reduced functionality of ER but a significant role for AR in MBC [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation